Does financial efficiency modify CO2 emission? Using panel ARDL-PMG in the case of five selected ASEAN countries - Mohamad Azmin Nur Azwani; Abdul Manaf Suhaily Maizan; Abdul Ghani Rosmaiza (BIO Web of Conferences, 2023)
Financial efficiency reduces carbon emissions by optimising resource usage, encouraging innovation and investment in low-carbon technology and solutions, and increasing transparency and accountability. This study examined the short- and long-term equilibrium relationships between CO2 emissions, financial efficiency, GDP, and energy consumption in five ASEAN nations from 1980 to 2020. Data stationarity was tested using the panel unit root test. The Autoregression Distribution Lag Pooled Mean Group (ARDL-PMG) model is best for empirical research because the data are long time series. The ARDL-PMG model shows that all variables affect CO2 emissions in the short term. Gross domestic product per capita and energy use affect CO2 emissions but not financial efficiency over time.